Cassiodoro Senatore: Complexiones in epistulis Pauli apostoli. Edited by Paolo Gatti - Winterbottom, Michael (The journal of theological studies, 2010)
‘In this chapter he commends charity in every respect, going so far as to assert that no virtue is of any use without it. He also defines what charity rejects, what it pursues; for though other gifts, i.e. faith and hope, are at rest in the age to come, charity alone lasts for ever; and he says it is altogether to be awaited.’ This is Cassiodorus’ summary of a celebrated chapter of 1 Corinthians. It makes no attempt to fit the chapter into its context, and leaves out the rhetoric, the passion, and the sublimity; instead, as the preface to the whole work puts it, it provides a ‘narration’ briefly ‘embracing’ (complectens) the most important points made by the apostle.